Effect of miR-200c on inducing autophagy and apoptosis of HT22 cells from mouse hippocampal neurons via regulating PRDM1 protein: a bioinformatics analysis - W. Wu; J. Fu; Q. Liu; Q. Wang; S. Gao; X. Deng; C. Shen (The European Zoological Journal)
To reveal the changes in microRNA (miRNA) expression profile in the hippocampus of mice with deep hypothermic circulatory arrest (DHCA) through bioinformatics analysis. The Support Vector Machine (SVM) algorithm in the Weka software was used to process, model, and screen the available miRNA data. This step included data preprocessing as well as SVM model construction and training to identify miRNAs associated with DHCA-induced brain injury. For the screened differentially expressed genes, gene ontology (GO) functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed to reveal the potential roles of these genes in biological processes and pathways. Quantitative reverse transcriptase PCR (qRT-PCR) was adopted to validate expressions of miRNAs, and a dual luciferase reporter assay was conducted to verify the relationship with the target gene. The results of the Venn diagram showed that 696 shared miRNAs were selected eventually as target genes for further research. Finally, the top 30 miRNAs with the highest differential expression intensities in DHCA-induced cerebral injury were identified in descending order of expressions. GO functional and KEGG pathway enrichment analyses on the screened differentially expressed genes revealed a possible correlation between PR/SET domain 1 (PRDM1), the target gene of miR-200c, and DHCA-induced cerebral injury. The results of the dual luciferase reporter assay indicated that miR-200c interacted with and bound to the 3’-UTR region of its target gene PRDM1 promoter. The apoptosis rate was the highest in HT22 cells of the Pre-miR-200c group, and the lowest in the Lenti-miR-200c group. Meanwhile, the protein and gene expressions of PRDM1 were the highest in the Lenti-miR-200c group, and the lowest in the Pre-miR-200c group. miR-200c binds to the 3’-UTR of PRDM1, further upregulating the expression of PRDM1 and affecting cell apoptosis, thereby playing a neuroprotective role.